2021
DOI: 10.14814/phy2.14724
|View full text |Cite
|
Sign up to set email alerts
|

Choice of cystometric technique impacts detrusor contractile dynamics in wistar rats

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 63 publications
2
7
0
Order By: Relevance
“…2 E). This bursting pattern of EUS activity found in sham animals is characteristic of that found in spinally intact animals in the literature, including our previously published reports 23 , 24 . For shams, the mean voided volume was 0.53 ± 0.06 ml, ICI duration 109.1 ± 40.9 s, in–out ratio 0.98 ± 0.22 and, 3.2 ± 0.33 s burst duration (Supplemental Table 1 ).…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…2 E). This bursting pattern of EUS activity found in sham animals is characteristic of that found in spinally intact animals in the literature, including our previously published reports 23 , 24 . For shams, the mean voided volume was 0.53 ± 0.06 ml, ICI duration 109.1 ± 40.9 s, in–out ratio 0.98 ± 0.22 and, 3.2 ± 0.33 s burst duration (Supplemental Table 1 ).…”
Section: Resultssupporting
confidence: 82%
“…3 C) occurred during L3 scES. Previous data also shows that a higher in/out ratio is a consequence of longer EUS bursting periods 23 . The frequency dependent increase of the in–out ratio in this study is consistent with those observations (Fig.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…As further support for the results obtained with the behavioral evaluations, we performed cystometric 22 and electromyographic evaluations of the external urethral sphincter 18 in rats from all groups. It is complicated to compare these results with previous studies using, for instance, a contusion SCI model, 23 nonetheless we found no differences for the duration of IPHFO, voiding volumes, threshold pressure or amplitude of the electromyographic response among the four groups, although the SCI‐BoNT/A rats show a trend towards improved CMG/EMG parameters.…”
Section: Discussionmentioning
confidence: 63%
“…The variability of these results was very large and may also be explained in part by disturbances in the detrusor caused by the implantation of the catheter. 15 , 26 …”
Section: Discussionmentioning
confidence: 99%